Design and implementation of packet forwarding engine for reconfigurable routers - Yi-jiao CHEN; Ze-xin LU; Zhi-gang SUN; Tao LI; Gao-feng LV (Tongxin xuebao)
The packet forwarding engine should provide not only the basic packet switching function,but also the reconfigurable ability for supporting the network processing functions evolving with time and space.Aiming at the above requirements,a component reconfiguration model of packet forwarding engine for the reconfigurable routers was proposed,and the program/circuit component running environment consisting of FPGA and network processers was designed and implemented based on the Pass-Through mode.The system implementation and application experimental results show that the packet forwarding engine for reconfigurable routers can support flexibly reconfiguration and mapping for the diverse service components,and it can provide high throughput and low-latency packet forwarding ability.